COMPREHENSION DEVELOPMENT ABOUT THE NAMES AND CHARACTERS OF ALLAH PROPHETS of SMPN PANTI STUDENTS CLASS VIIIB JEMBER DISTRICT BY RELIGION MUSIC MEDIA AND BAROK - Mariyatul Qibtiyah (FKIP Universitas Islam Jember, 2013)
Abstract: comprehension development about the names and characters of Allah prophets of SMPN Panti students class VIII b Jember district by religion music media and barok. In the context nowadays, the most important purpose in education field is developing mental ability that may people could be learn to developing the comprehension of Allah prophets names and their characters, it needs to design the learning environment, by using religion music media and barok as one of it. This research is objecting to describe about how far the usage of religion music media and barok can developing process and result about the names and characters of Allah prophets in Islamic education subject. The evaluation of process and learning results can be done by using learning result test, observation, interview and quest nary. The learning result showing that after students class VIIIb had follow the learning process by using Islamic music and barok as the media had been brought the result of comprehension development about the names and characters of Allah prophets that is before the act ,class VIIIb just have average value 6,79 and at cycle 1 the value increase to be 76,22 but haven’t reach the target value yet. Then, continued at cycle 2,at cycles 2 the value increasing to be 81,75 so that in cycle 2 the expected target had been reached. Meanwhile, for the result observation of student activity in cycle 1 average score reaches 90% with GOOD category. And for the observation of teacher activity 85% with GOOD category.At cycle 2 the observation score result of student increased to be 95% with EXCELENT category. And for teacher activity observation increased to be 95% with good category. With this reflection of action on cycle 2 has reached the primary target.From the result of the learning above, the teacher are suggested to watch the factor that support in learning process in teaching action, with the result the student isn’t easier to be bore and keep have fun or more like to learn. This discoverer just on islamic education only in SMPN 2 Panti Jember Grade 8thB. I hope it can develope in widely and deeply on next research.Keywords: The names and the character of Allah’s Prophet, the media of religion music and barok